The compensation incentive effect of athletes: A structural equation model - Zhao, Huan; Liu, Zhaoxia; Zhang, Susu; Xiao, Feiyan; Liu, Meng; Li, Ruiyuan; Zhang, Liqing; Xu, Chengcheng (Frontiers in Psychology, 2022)
This study explores the compensation incentive effect of athletes. Based on the related literature, we proposed theoretical hypotheses on the compensation incentive effect and established an assessment index system of the compensation incentive effect for athletes. A structural equation model was used to test the survey data of 352 athletes in six provinces to discover the truth of the compensation incentive effect. The results suggested that direct economic compensation satisfaction, direct non-economic compensation satisfaction, and indirect non-economic compensation satisfaction had significant positive effects on the compensation incentive effect of athletes, while indirect economic compensation satisfaction showed no significant effect. Moreover, the evaluation results of athletes’ compensation incentive effect showed that direct economic compensation satisfaction contributed the most to the influence factor of the compensation incentive effect. Therefore, the evaluation of athletes’ compensation incentive effect should focus on variables of direct economic compensation satisfaction, i.e., basic compensation satisfaction, bonus income satisfaction and subsidy satisfaction. Finally, some strategies and recommendations were suggested to improve the compensation design for athletes.